Aspirations of freshmen and expectations of seniors in the College of Agriculture at Kansas State University - Parks, Amanda (Kansas State University, 2016)
Agriculture is one of the fastest growing industries in the world. Universities have the opportunity to meet the growing demand for more agricultural graduates. To better understand how to facilitate students in degree completion at Kansas State University, this study looked at the aspirations of freshmen and the expectations of seniors within the College of Agriculture at Kansas State University. The sample included 517 freshmen and 196 seniors, for a total of 713 students who completed the questionnaire. Both freshmen and seniors indicated positivity toward future career goals. Additionally, both groups indicated having participated or the desire to participate in a student organization within the College of Agriculture, and to complete an internship relevant to their major. Intrinsic values, such as relevance to their interests and personal values, were influential in choice of degree for both freshmen and seniors. Both groups responded very positively about future job opportunities and preparedness for the career force. Freshmen and Seniors were relatively consistent in their predication of salary one year and five years after graduation, however freshmen had higher expectations 10 years post-graduation. Forty-two percent (n = 210) of freshmen indicated that they had thought about changing majors, while 29.2% (n = 56) of seniors had responded that they had changed majors during their academic career. Both groups indicated that they had a positive college experience at Kansas State University. According to this research, Kansas State University students need more information about job opportunities and salary expectations. Additionally, more information regarding majors will help students choose a major most connected to their personal interests.
Keywords: College of Agriculture; Aspirations; Expectations; Barriers to employment; CommitmentRetention